Improving Student Learning Outcomes Through the Scientific Approach Method in the Hadith Studies Subject for Grade XI Religious Class at MA Unggulan K.H. Abd. Wahab Hasbulloh Tambak Beras Jombang - Purbaningrum, Ajeng; Prihatiningtyas, Suci; Husna, Asiyah Lu'Lu'ul; Darmawan, Faridl (LPPM Universitas KH. A. Wahab Hasbullah, 2024)
The science of hadith plays a crucial role in Islamic education, aiding in the interpretation and clarification of Quranic teachings. This study investigates the impact of implementing a scientific approach in teaching Hadith Science at MA Unggulan K.H. Abd. Wahab Hasbulloh. Using a pre-experimental design with 34 students, pretest and posttest scores were analyzed to assess learning outcomes. Results indicate significant improvement post-implementation, with most students achieving